Exposure of FVIII in the Presence of Phosphatidyl Serine Reduces Generation of Memory B‐Cells and Induces Regulatory T‐Cell‐Mediated Hyporesponsiveness in Hemophilia A Mice. Issue 8 (2nd June 2015) - Ramakrishnan, Radha; Davidowitz, Andrew; Balu‐Iyer, Sathy V.
<x xml:space="preserve">Abstract</x> A major complication of replacement therapy with Factor VIII (FVIII) for hemophilia A (HA) is the development of unwanted immune responses. Previous studies showed that administration of FVIII in the presence of phosphatidyl serine (PS) reduced the development of anti‐FVIII antibodies in HA mice. However, the impact of PS‐mediated effects on immunological memory, such as generation of memory B‐cells, is not clear. The effect of PS on memory B‐cells was therefore investigated using adoptive transfer approach in FVIII−/− HA mice. Adoptive transfer of memory B‐cells from a PS‐FVIII‐treated group to naïve mice followed by challenge of the recipient mice with FVIII showed a significantly reduced anti‐FVIII antibody response in the recipient mice, compared with animals that received memory B‐cells from free FVIII and FVIII‐charge matched phosphatidyl glycerol (PG) group. The decrease in memory B‐cell response is accompanied by an increase in FoxP3 expressing regulatory T‐cells (Tregs). Flow cytometry studies showed that the generation of Tregs is higher in PS‐treated animals as compared with FVIII and FVIII‐PG treated animals. The PS‐mediated hyporesponsiveness was found to be antigen‐specific. The PS‐FVIII immunization showed hyporesponsiveness toward FVIII rechallenge but not against ovalbumin (OVA) rechallenge, an unrelated antigen. This demonstrates that PS reduces immunologic memory of FVIII and induces antigen‐specific peripheral tolerance in HA mice. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2451–2456, 2015